Police Training in Practice: Organization and Delivery According to European Law Enforcement Agencies - Kleygrewe, Lisanne; Oudejans, Raôul R. D.; Koedijk, Matthijs; Hutter, R. I. (Vana) (Frontiers in Psychology, 2022)
Police training plays a crucial role in the development of police officers. Because the training of police officers combines various educational components and is governed by organizational guidelines, police training is a complex, multifaceted topic. The current study investigates training at six European law enforcement agencies and aims to identify strengths and challenges of current training organization and practice. We interviewed a total of 16 police instructors and 7 police coordinators with conceptual training tasks. A thematic analysis (Braun & Clarke, 2006; Terry et al., 2017) was conducted and results organized in the two main themes evident across all six law enforcement agencies: organization of training and delivery of training. Results show that governmental structures and police executive boards are seen as the primary authorities that define the training framework in which police instructors operate. These administrative structures regulate distant and immediate resources, such as available training time, training facilities, equipment, and personnel. Within the confines of available resources and predetermined training frameworks, results indicate that police instructors thoroughly enjoy teaching, creating supportive and motivating learning environments, and applying their personal learning perspectives to training. Nonetheless, police instructors are critical of the level of training they are able to achieve with the available resources.